Síntese de óxidos nanoestruturados de CuO/Cu2O por spray pirólise micro-ondas - Cancellieri, Igor Charaba (Universidade Federal de São Carlos, 2023)
The advancement of science and technology at the nanoscale boosted an increase in the nanostructured ceramic materials applications, from the manufacture of electronic components to scaffolds for human bones development. Amongst these materials, metallic oxides are of particular interest due to the range of possible applications, notoriously optical, electrical, and magnetic properties. Uniting their properties with quantum effects related to the nanoscale, materials with high performance (i.e., improved properties) or even new applications (i.e., new or atypical properties, not found in their bulk equivalent) find important employability in the modern industry. Consequently, there is a great demand for more efficient and green synthetic techniques, combining production, speed and lowers costs. Spray pyrolysis is one of most important technique in this group by its low cost and high efficiency in the production of powders and nanostructured films, well known in the manufacture of photovoltaic cells, catalytic processes, among other diverse applications related to film formation and nanostructured material production. In face of its potential, this study focusses on the development of spray pyrolysis by using microwave as a heating source for the synthesis of CuO/Cu2O, to improve the technique efficiency and green status.
Synthesis of nanostructured CuO/Cu2O oxides by microwave spray pyrolysis
Keywords: Spray pirólise; Óxidos metálicos; Micro-ondas; Síntese; Spray pyrolysis; Metal oxides; Microwave; Synthesis; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS